2022
DOI: 10.5334/jbsr.2812
|View full text |Cite
|
Sign up to set email alerts
|

Sinus Disease Grading on Computed Tomography Before and After Modulating Therapy in Adult Patients with Cystic Fibrosis

Abstract: Objectives: Cystic fibrosis transmembrane conductance regulator (CFTR) modulator therapy effects on respiratory function, pulmonary exacerbations and quality of life have been well documented. However, CFTR modulator therapy effects on sinus disease have not been so well reported. A previous study reported that ivacaftor improves appearance of sinus disease on Computed Tomography (CT) in cystic fibrosis (CF) patients with G551D mutation. The aim of this study was to evaluate the effect of CFTR mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
1
5
0
1
Order By: Relevance
“…The recently approved triple combination therapy is a potential treatment for many patients who had previously been excluded from CFTR modulation therapy, and previously published articles showed that ETI improves both symptoms and radiological findings of sinonasal disease. [1][2][3] ESS is a minimally invasive procedure performed through the nostrils that consists of enlarging sinus ostia, removing causes of sinus blockage, such as nasal polyps, and restoring adequate aeration of sinuses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The recently approved triple combination therapy is a potential treatment for many patients who had previously been excluded from CFTR modulation therapy, and previously published articles showed that ETI improves both symptoms and radiological findings of sinonasal disease. [1][2][3] ESS is a minimally invasive procedure performed through the nostrils that consists of enlarging sinus ostia, removing causes of sinus blockage, such as nasal polyps, and restoring adequate aeration of sinuses.…”
Section: Discussionmentioning
confidence: 99%
“…Sinonasal involvement causes frequent symptoms and a significant quality of life worsening in CF patients. The recently approved triple combination therapy is a potential treatment for many patients who had previously been excluded from CFTR modulation therapy, and previously published articles showed that ETI improves both symptoms and radiological findings of sinonasal disease 1–3 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Shortly after the introduction of IVA, the first reports indicated not only amelioration in pulmonary health but also notable improvements in cystic fibrosis-related secondary chronic rhinosinusitis (CRS), especially in patients with at least one G551D gating mutation (11) . Studies on ELX/TEZ/IVA, both prospective and retrospective, revealed substantial reductions in sinonasal complaints and radiographical disease severity (12)(13)(14)(15)(16)(17)(18)(19) . To date, no clinical data are available on the impact of TEZ/IVA dual therapy on CF-related secondary CRS or the effect of modulator therapy on nasal endoscopy or bacterial upper airway colonization.…”
Section: Introductionmentioning
confidence: 99%